Pendekatan Al-Qur’an, Hadis, dan Bahasa Keagamaan dalam Bimbingan Perkawinan di KUA Panyabungan Utara: Perspektif Manajemen Dakwah - Azhar, Jamalul; Batubara, Hafsah Juni; Tama, Annisa; Nur, Hakimah; Hidayat, Rahmat; Sari, Nurlela; Huda, Nurul; Wardah, Siti; Sakinah, Putri; Yunus, Muhammad (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the approaches of the Qur’an, Hadith, and the use of religious language in marriage guidance at KUA Panyabungan Utara from the perspective of da'wah management. This research employs a qualitative method with a descriptive approach through interviews, observations, and documentation. The findings indicate that the Qur’an and Hadith serve as the primary foundations in delivering the material, while religious language is adapted to the social conditions of prospective brides and grooms to ensure it is communicative and easily understood. The implementation of guidance has applied da'wah management functions, including planning, organizing, implementation, and evaluation, thereby contributing to improving the spiritual and social readiness of prospective couples. The da'wah management perspective reveals how theological messages are designed and conveyed effectively to address psychological and sociological aspects of society. The novelty of this study lies in the synthesis of normative values and the managerial functions of KUA as a structured da'wah institution, with religious language acting as a persuasive medium. These findings are expected to offer an innovative model for marriage guidance based on religious rhetoric and local wisdom